Regulation of Non-coding RNAs in Heat Stress Responses of Plants - Zhao, Jianguo; He, Qingsong; Chen, Gang; Wang, Li; Jin, Biao (Frontiers in Plant Science, 2016)
Heat stress is an important factor limiting plant growth, development, and productivity; thus, plants have evolved special adaptive mechanisms to cope with high-temperature stress. Non-coding RNAs (ncRNAs) are a class of regulatory RNAs that play an important role in many biological processes. Recently developed advanced technologies, such as genome-wide transcriptomic analysis, have revealed that abundant ncRNAs are expressed under heat stress. Although this area of research is still in its infancy, an increasing number of several classes of regulatory ncRNA (i.e., miRNA, siRNA, and lncRNA) related to heat stress responses have been reported. In this mini-review, we discuss our current understanding of the role of ncRNAs in heat stress responses in plants, especially miRNAs, siRNAs, and their targets. For example, the miR398-CSD/CCS-HSF, miR396-WRKY6, miR159-GAMYB, and TAS1-HTT-HSF pathways regulate plant heat tolerance. We highlight the hormone/development-related miRNAs involved in heat stress, and discuss the regulatory networks of miRNA-targets. We also note that DNA methylation and alternative splicing could affect miRNA expression under heat stress, and some lncRNAs could respond to heat stress. Finally, we briefly discuss future prospects concerning the ncRNA-related mechanisms of heat stress responses in plants.